PENGEMBANGAN DESA WISATA BERBASIS DAYA TARIK WISATA PETUALANGAN PADA MASA PANDEMI COVID-19 DI BALI - Prasiasa, Dewa Putu Oka (Jurnal Master Pariwisata (JUMPA); Volume 09, Nomor 02, Januari 2023DO - 10.24843/JUMPA.2023.v09.i02.p01, 2023)
This study examines the strengths, weaknesses, opportunities and challenges of tourist villages in Bali; find important criteria in the development of tourist villages in Bali; and formulate strategic priorities for the development of tourist villages in Bali that offer adventure tourism attractions during the Covid-19 Pandemic. As a qualitative study, data analysis was carried out using SWOT, AHP, and a combination of SWOT and AHP. This study found that tourist villages with adventure tourism attractions during the Covid-19 Pandemic in Bali had strengths: variations in tourist attractions, community readiness to accept tourists during the Covid-19 Pandemic, people were easy to adapt, the implementation of health protocols was understood by the community; Weaknesses: public transportation to tourist villages, access is not well organized, tourist attractions are relatively the same; opportunities: potential to attract tourists, nature and culture support the development of tourist villages; and threats: digital technology in marketing tourism village products has not been evenly distributed, the entry of foreign investors into tourist villages. Three important criteria in the development of tourist villages during the Covid-19 Pandemic in Bali: concern for CHSE (score 0.351), security guarantees (score 0.34), and ease of CHSE facilities (score 0.329). Meanwhile, three strategic priorities need to be implemented: healthy tourism (score 0.89), sports tourism (score 0.67) and environmentally friendly tourism (score 0.58). Keywords: tourism village; adventure tourism; tourist attraction; covid-19 pandemic.